Melanoma trials that defined surgical management: Brief overview of current/upcoming adjuvant/neoadjuvant trials. Issue 1 (13th December 2021) - Patel, Ankit; Skitzki, Joseph
Abstract: Adjuvant systemic therapy for cutaneous melanoma has experienced practice‐changing shifts over the last decade. The successful results of immunotherapies and targeted therapies in the metastatic setting have allowed for investigative trials of the same therapies in the adjuvant and now neoadjuvant setting, with the potential for improved clinical outcomes in patients with high risk resected Stage III and IV melanoma.